EFL Teachers’ Perceived Efficacy of Digital Platforms in Varied Online English Classes in a Higher Education - Masitoh, Fitriatul; Fitriyah, Ima; Mumtaza, Irma Khairany (Journal of Languages and Language Teaching, 2024)
As the Covid-19 pandemic progressed, such measures disrupted schools and universities. Leaders of educational institutions identified online learning as the best option for students and teachers to continue their education when they were unable to attend school. Although EFL students' and teachers’ attitudes toward online learning were much discussed in the context of higher education, little evidence addresses how EFL teachers practice digital platforms in various EFL programs. This study aimed to investigate numerous digital platforms utilized by EFL teachers for online learning and the purposes in using those platforms. It also tried to find out the most frequently used platforms during the pandemic. Using a qualitative approach, this study involved ten EFL teachers from the English Education Program and non-English Education Programs (General English and ESP) of all faculties in a state Islamic institute in Indonesia. Through a closed and open questionnaire, this study found that all EFL teachers combined multiple digital platforms (the college’s e-learning platform developed from Moodle, WhatsApp group, YouTube, Google Form, Google Meet, Zoom meeting, Google Drive, Socrative, and Quizziz) for various purposes in online classroom activities. In addition, college’s e-learning platform developed from Moodle, WhatsApp group, and YouTube were found to be the most frequently used due to the benefits for online learning. In light of these findings, a discussion of the research implications for institutions of higher education and potential future researchers is presented.